Environmental economics : theory and policy - Endres, Alfred. 4 0 16; 5 (Cambridge : Cambridge University Press, 2011)
This intermediate-level undergraduate textbook in environmental economics builds on the microeconomics courses students take in their first year. It intentionally does not survey the whole field or present every possible topic. Instead, there is a clear focus on the theory of environmental policy and its practical applications. Most of the applied parts of the book deal with the economics of environmental policy in the European Union and in the United States. The book combines basic environmental economic analysis, such as the internalization of externalities, with recent developments in this field, including induced technical change and coalition theory. Moreover, topics from daily policy debates such as global warming are put into economic perspective. This is done in an intelligible form for advanced undergraduate students of economics, business administration, and related fields. Each part of the book contains a set of exercises and suggested solutions--;This intermediate-level undergraduate textbook in environmental economics builds on the microeconomics courses students take in their first year. It intentionally does not survey the whole field or present every possible topic. Instead, there is a clear focus on the theory of environmental policy and its practical applications. Most of the applied parts of the book deal with the economics of environmental policy in the European Union and in the United States. The book combines basic environmental economic analysis, such as the internalization of externalities, with recent developments in the field, including induced technical change and coalition theory. Moreover, topics from daily policy debates such as global warming are put into economic perspective. This is done in an intelligible form for advanced undergraduate students of economics, business administration, and related fields. Each part of the book contains a set of exercises and suggested solutions--
Machine generated contents note: Part I. The Internalization of Externalities as Central Theme of Environmental Policy: 1. Foundations; 2. Implications of making the concept of internalization programmatic in environment policy; Part II. Strategies for Internalizing Externalities: 3. Negotiations; 4. Environmental liability law; 5. Pigovian tax; Part III. Standard-Oriented Instruments of Environmental Policy: 6. Introduction; 7. Types of environmental policy instruments; 8. Assessment of environmental policy instruments; Part IV. Extensions of the Basic Environmental-Economics Model: 9. Environmental policy with pollutant interactions; 10. Environmental policy with imperfect competition; 11. Internalization negotiations with asymmetrical information; 12. The 'double dividend' of the green tax; 13. The induction of advances in environmental technology through environment policy; Part V. International Environmental Problems: 14. Introduction; 15. International environmental agreements; 16. Instruments of international environmental policy - the example of the EU's emissions trading; 17. Epilogue: the vision of a federal US emission trading system; Part VI. Natural Resources and Sustainable Development: 18. Resource exhaustion - the end of mankind?; 19. Renewable resources; 20. Sustainable development; Epilogue: three types of externality and the increasing difficulty of internalizing them.
Includes bibliographical references and index.
Translated from the German.
Keywords: 2 -- 0; 6; Environmental economics. -- 20; 20; 2